Hemodynamic Analysis Using 4D Flow MRI in a Case of Aortic Dissection With Aberrant Right Subclavian Artery - Kenji Sakakibara; Hiroyuki Nakajima; Yukiyo Yoshida; Yudai Hagihara; Chie Nakamura; Daichi Shikata; Yuki Takesue; Satoru Shiraiwa; Yoshihiro Honda; Shigeaki Kaga; Masahiro Hamasaki; Hisashi Johno; et al. (Clinical Case Reports)
ABSTRACT Four‐dimensional flow magnetic resonance imaging (4D flow MRI) was utilized to analyze an aortic dissection with an aberrant right subclavian artery, revealing vortex formation and an increased oscillatory shear index (OSI), both indicative of variations in wall shear stress. An elevated OSI has been associated with an elevated risk of aortic dissection.